2022
DOI: 10.5194/isprs-archives-xlvi-2-w1-2022-9-2022
|View full text |Cite
|
Sign up to set email alerts
|

A Procedure to Import a Complex Geometry Model of a Heritage Building Into Bim for Advanced Architectural Representations

Abstract: Abstract. The aim of this communication is to present the advantages and disadvantages of a Scan-to-BIM process applied to a heritage building in order to obtain advanced technical drawings to be used in the analysis and illustration of the project. The whole process described includes: the survey planification and data acquisition with a Terrestrial Laser Scanner; the processing and cleaning of the point cloud; the 3D mathematical modelling; a proposal for semi-automatic modelling of organic elements; and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…"Scan-to-BIM" is a reverse-engineering process involving Realty-Based 3D models (i.e., LiDAR and photogrammetric point clouds) used as a reference to manually or, possibly semi-automatically [21], develop an information model suitable to be used for monitoring and scheduled management of a building, particularly focusing on the digitisation of Cultural Heritage. Overlaying all the surveys carried out in the period 2019-2022, the elements that make up the various parts of the Theatre complex have been modelled in Autodesk Revit: the blocks that form the steps and stairs of the Ima and Media Cavea; the complex shapes of the galleries on both sides of the Orchestra; the walls that made up the Pulpitum; and the structures of the Scaenae Frons, the decorated architectural backdrop of the stage.…”
Section: Methodsmentioning
confidence: 99%
“…"Scan-to-BIM" is a reverse-engineering process involving Realty-Based 3D models (i.e., LiDAR and photogrammetric point clouds) used as a reference to manually or, possibly semi-automatically [21], develop an information model suitable to be used for monitoring and scheduled management of a building, particularly focusing on the digitisation of Cultural Heritage. Overlaying all the surveys carried out in the period 2019-2022, the elements that make up the various parts of the Theatre complex have been modelled in Autodesk Revit: the blocks that form the steps and stairs of the Ima and Media Cavea; the complex shapes of the galleries on both sides of the Orchestra; the walls that made up the Pulpitum; and the structures of the Scaenae Frons, the decorated architectural backdrop of the stage.…”
Section: Methodsmentioning
confidence: 99%
“…On the other side, commercial components usually ensure longer-term support and more stability, but this comes at a higher price. The modelling phase is undoubtedly time-consuming if carried out with manual methods, a reality-based approach, and high accuracy (Acosta et al, 2022;Spettu et al, 2021). A possible solution is using the point clouds as the geometrical basis.…”
Section: Open Issues and Possible Developmentsmentioning
confidence: 99%
“…On the other hand, scan-to-BIM is still mainly a time and effortconsuming manual process (Rocha et al, 2020), usually employing the generation of specifically developed parametric objects (Chiabrando et al, 2017). Therefore, several experiments concerning automatic surface recognition (Romero-Jarén and Arranz, 2021; Sun et al, 2022) and NURBS modelling of historic architectural decorative apparatuses (Acosta et al, 2022;Barazzetti et al, 2015) can be found in the literature. This kind of application additionally entails a certain degree of automatisation, variously employing Artificial Intelligence (AI) algorithms for automatic segmentation and semantisation of the survey database (Teruggi et al, 2021).…”
Section: The Scan-to-bim Workflowmentioning
confidence: 99%